Zasięg organizacyjny reformy. (Ciechanów : [s.n.], 1981)
Afisz propagandowy.
Keywords: Propaganda -- Polska -- 1970-2000 -- druki ulotne; Polska -- polityka i rządy -- 1945-1981 -- druki ulotne; Druki ulotne -- 1970-2000.